Efektivitas Program Pekarangan Pangan Lestari (P2L) Kelompok Wanita Tani Di Kota Pekanbaru - Utari, Mustika Fitri; Mayarni Mayarni (Lembaga Pengkajian Dan Pengembangan Sumberdaya Pembangunan (lppsp), 2023)
Program Effectiveness is an assessment or measurement of the extent to which the activities in the programs that have been carried out can achieve the initial objectives of the program. The success of a program can be seen in the effectiveness of achieving the goals that have been previously planned by the related organizations. The Sustainable Food Yard Program (P2L) is an activity carried out by the Food Security Agency. This activity aims to realize diversification of food consumption to meet the nutritional needs of the community in accordance with local potential and wisdom in order to create a healthy, active and productive life and to know the inhibiting factors in its management. This study uses Sutrisno's theory in Nuraida which uses five indicators, namely, Program Understanding, On Target, On Time, Goals Achieved, and Real Change. The research method used in this study used descriptive qualitative methods and data collection techniques through primary and secondary data sources obtained through the process of observation or observation, interviews, and documentation by researchers and then analyzed. The results showed that the Sustainable Food Pekarangan (P2L) program had been carried out according to the plan, but there was a problem in terms of communication between Women Farmer Group members due to the large number of members so they had to be able to manage communication so that the Sustainable Food Yard program (P2L) could run smoothly. smoothly and has a positive impact.